2021
DOI: 10.1021/acs.est.1c03493
|View full text |Cite
|
Sign up to set email alerts
|

Rat Metabolism Study Suggests 3-(3,5-Di-tert-butyl-4-hydroxyphenyl)propionic Acid as a Potential Urinary Biomarker of Human Exposure to Representative 3-(3,5-Di-tert-butyl-4-hydroxyphenyl)propionate Antioxidants

Abstract: propionate antioxidants, a family of synthetic phenolic antioxidants (SPAs) widely used in polymers, have recently been identified in indoor and outdoor environments. However, limited information is available concerning human exposure to these novel contaminants. In the present study, seven 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate antioxidants were analyzed in human urine samples of donors from the United States. None of the target SPAs were initially detected in the urine samples either before or after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This compound can be further oxidized into 7,9-di- tert -butyl-1-oxaspiro(4,5)deca-6,9-diene-2,8-dione ([M + H] + 173.9 Å 2 , [M + Na] + 185.2 Å 2 ). 48 Many of the TW CCS N2 values of degradation products are reported here for the first time, which contribute a lot to the application of IMS in the analysis of FCCs.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…This compound can be further oxidized into 7,9-di- tert -butyl-1-oxaspiro(4,5)deca-6,9-diene-2,8-dione ([M + H] + 173.9 Å 2 , [M + Na] + 185.2 Å 2 ). 48 Many of the TW CCS N2 values of degradation products are reported here for the first time, which contribute a lot to the application of IMS in the analysis of FCCs.…”
Section: Resultsmentioning
confidence: 71%
“…3-(3,5-Di- tert -butyl-4-hydroxyphenyl)­propionic acid ([M + Na] + 175.6 Å 2 ) can be produced from Irganox 245, Irganox 1076, Irganox 1035, and Irganox 1098. This compound can be further oxidized into 7,9-di- tert -butyl-1-oxaspiro­(4,5)­deca-6,9-diene-2,8-dione ([M + H] + 173.9 Å 2 , [M + Na] + 185.2 Å 2 ) . Many of the TW CCS N2 values of degradation products are reported here for the first time, which contribute a lot to the application of IMS in the analysis of FCCs.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…More details of exposure design and all sequences data have been described in our previous work . The quantification method and measured concentrations of 2,6-DTBP and 2,6-DTBQ in mice livers and serums are provided in Text S1 and Table S1. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis was performed based on differential expressed genes (DEGs) induced by 2,6-DTBP and 2,6-DTBQ.…”
Section: Methodsmentioning
confidence: 99%
“…On one hand, PAHs have been shown to induce the phase I enzymes (e.g., CYPs) and alter the metabolite profile (e.g., (1+2)-/4-OH-PHEs ratio). , In this study, we observed increased (1+2)-/4-OH-PHEs ratios from the nonheating to heating seasons, in association with personal exposure to PAHs (Figure S4), suggesting a possible seasonal difference in CYP activities. On the other hand, PAHs have been shown to inhibit phase II enzymes (e.g., glucuronosyltransferases), which may potentially slow the urinary excretion of OH-PHEs and 2-PHECA, since we and others have previously shown that a predominant fraction of hydroxylated and carboxylic acid metabolites were in conjugated forms. ,, Unfortunately, in the present, we did not assess the fraction of conjugated metabolites, so the direct evidence supporting the phase II metabolic alteration is lacking.…”
Section: Resultsmentioning
confidence: 67%